Intergenerational persistence in educational attainment in Italy - Daniele Checchi; Carlo V. Fiorio; Marco Leonardi (Institute for the Study of Labor (IZA), 2008)
In this paper we show that there is a reduction in the correlation coefficient between father and children schooling levels over time in Italy. However, focusing on equality of circumstances, we show that there is still a persistent difference in the odds of attaining a college degree between children of college educated parents and children of parents with lower secondary education attainment. The explanation of these trends lies in differential impact of liquidity constraints and risk aversion. Some descriptive evidence on the persistent differential in returns to college education depending on father's education is also provided.
urn:nbn:de:101:1-2008081255
Keywords: J62; 330; Educational attainment; Italy; family background; Bildungsabschluss; Generationenbeziehungen; Bildungschancen; Familiensoziologie; Italien